2023
DOI: 10.1002/dys.1747
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Working Memory‐Balance program training alters the left fusiform gyrus resting‐state functional connectivity: A randomized clinical trial study on children with dyslexia

Abstract: Sufficient activation of the left fusiform gyrus is important in reading ability acquisition due to its role in reading and naming, working memory (WM), and balance tasks. Recently, a newly‐designed training program, Verbal Working Memory‐Balance (VWM‐B), has been evaluated on children with dyslexia, and its positive effects were shown on reading ability, WM capacity, and postural control. In the present study, we aimed to estimate the functional connectivity alterations of the left fusiform gyrus following tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 121 publications
3
17
0
Order By: Relevance
“…All 27 children were assigned to either the active control group or the experimental group, with the active control group consisting of 12 children with DD and the experimental group containing 15 children with DD. The study sample size was consistent with past comparable studies [2,60]. A post-hoc power analysis was also conducted to show the power of the current study sample size.…”
Section: Subjects and Designmentioning
confidence: 54%
See 4 more Smart Citations
“…All 27 children were assigned to either the active control group or the experimental group, with the active control group consisting of 12 children with DD and the experimental group containing 15 children with DD. The study sample size was consistent with past comparable studies [2,60]. A post-hoc power analysis was also conducted to show the power of the current study sample size.…”
Section: Subjects and Designmentioning
confidence: 54%
“…Among computer-based training programs evaluated in DD, some positive effects have been shown on EF [22,[57][58][59]. These training programs were usually single-task; however, it has been suggested that training by two or more modalities in combination would be more effective [2,22,60]. Dual-task training protocols can effectively modulate attention, EFs, and standing postural control in different populations [61][62][63].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations